Managerial Performance Study: The Role Of Management Accounting Information Systems Performance Measurement Systems And Reward Systems - Irfan, Irfan (CERED Indonesia Institute, 2024)
This study aims to test and analyze the influence of management accounting information systems, performance measurement systems and reward systems on managerial performance at PT. Medan Industrial Estate. The sampling technique used in this study is the saturated sampling technique, with the number of samples obtained as many as 32 samples. The data collection technique used in this study is a questionnaire, namely distributing questionnaires to managers, assistant managers and supervisors of PT KIM (Medan Industrial Estate). The data analysis techniques used in this study are outer model analysis, inner model analysis and hypothesis testing using Partial Least Square (PLS) software. The results of this study indicate that 1) Management Accounting Information Systems have a significant effect on managerial performance, 2) Performance Measurement Systems do not have a significant effect on managerial performance, 3) Reward Systems do not have a significant effect on managerial performance